Critical Criminology of Media Coverage on the Murder of Indonesian Embassy Staff in Peru - Givandra Anezka Putri Menggar; Fany N. R. Hakim (Information Technology and Science (ITScience), 2026)
Media coverage of the murder of an Indonesian Embassy staff member in Peru has generated diverse interpretations regarding the motives, characteristics, and context of the crime. This topic warrants scholarly attention, as media construction of criminal cases can shape public perception and social understanding of crime. Although studies on crime news construction have been widely conducted, prior research remains limited in examining cases with diplomatic and inter-state dimensions that simultaneously consider interpretations from both national and international media alongside actors responses, amid restricted information access and ongoing legal proceedings. This study aims to analyse how media coverage of this case produces diverse interpretations through the lens of critical criminology. A qualitative case study design was employed through digital observation, interviews, and literature review. The analysis draws on Richard Quinney’s Social Reality of Crime theory, specifically the propositions of definition of crime, construction of criminal conceptions, and the social reality of crime. The findings reveal that media outlets constructed the case through varied terminology, sources, and narratives, framing it as organised crime, mistaken identity, and geopolitical entanglement. These constructions shaped actor interpretations ranging from ordinary criminal acts, premeditated murder, transnational criminal networks, to international geopolitical interests. This interaction ultimately produced a social reality of crime that is dynamic and contextual, thus, this study demonstrates that crime is a social construction shaped through interpretation, power relations, and media narratives in the public sphere.